Effect of omega-3 dietary supplements with different oxidation levels in the lipidic profile of women: a randomized controlled trial. (11th July 2013) - García-Hernández, V. M.; Gallar, M.; Sánchez-Soriano, J.; Micol, V.; Roche, E.; García-García, E.
Abstract: The oxidation level of omega-3 fatty acid supplements commercialized in capsules may be a risk to consumers' health. For this purpose, we have designed a single-blind, parallel-group, randomized controlled trial in which 52 women participated. Volunteers were randomly distributed into three groups consuming: (1) less oxidized oil pills, (2) highly oxidized oil pills and (3) no capsules. All groups consumed a fish-rich diet. Circulating glucose, total cholesterol, triglycerides and glutamic pyruvic transaminase were determined at the beginning and end (30 days) of the study. As a result, the ingestion of less oxidized ω-3 supplements reduced circulating triglyceride and cholesterol levels, as opposed to the highly oxidized omega-3 capsules, which had a negative effect on cholesterol levels. In conclusion, the level of oxidation of the supplements is a key factor in controlling circulating lipid profile. Therefore, manufacturers must pay attention to the quality of the prime product prior to encapsulation.